Reality And Consequences of The Urbanization Phenomenon In Algeria - Boudia Leila , Djeffal Meriem (Migration Letters, 2024)
This study aims at showing that before colonization, Algeria was rurally dominated by a major nomad and semi-nomad population. Then, the successive political and military colonial actions led to in-depth changes in the spatial distribution of the population. In this line, the coastal cities included the communication infrastructure and the industrial units; therefore, their populations developed rapidly. Besides, the concentration in the coast and the rapid growth of the population increased hugely during the liberation revolution against the French colonization, which aimed at taking over the populations through putting them in groups. Thus, Algeria inherited an urban system that is characterized dedicated to the concession of the coast with a with a large concentration of the population in the North, unlike the relatively depopulated regions of High Plateaus and Southernmost that are relatively depopulated.